Role of a Tissue Factor Pathway Inhibitor, the Plasma Proteinase ADAMTS-13 and its Inhibitor in the Pathogenesis of Acute Respiratory Distress Syndrome in A/H1N1 Influenza - E. V. Prutkina; A. V Malyarchikov; N. N. Tsybikov; K. G. Shapovalov; N. V. Isakova (Общая реаниматология, 2011)
Objective: to study the role of a tissue factor pathway inhibitor (TFPI), the metalloproteinase ADAMTS-13, and its inhibitor in the pathogenesis of acute respiratory distress syndrome (ARDS) in A/H1N1 influenza. Subjects and methods. The study enrolled 52 patients of both sexes aged 19 to 40 years with different clinical forms of A/H1N1 influenza, of whom 14 patients developed Stages I-II ARDS in the presence of pneumonia. An enzyme immunoassay was used to estimate the concentrations of TFPI, ADAMTS-13, and its inhibitor, the antibodies of the IgG class. Results. The level of TFPI increased in parallel with the progression of the disease, its highest concentration was found in patients with ARDS-complicated influenza pneumonia. There was a higher relative activity of ADAMTS-13 in patients with moderate pneumonia while this enzyme was relatively deficient in those with ARDS-complicated pneumonia. Conclusion. Relative ADAMTS-13 deficiency is one of the triggers of ARDS in severe forms of pneumonia in the presence of A/H1N1 influenza. The high level of TFPI may predict the development of respiratory distress syndrome in pneumonia in the presence of influenza infection. Key words: A/H1N1 influenza, respiratory distress syndrome, tissue factor pathway inhibitor, ADAMTS-13.